2022
DOI: 10.1039/d2en00113f
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and depuration of Ag nanoparticles versus Ag ions by zebrafish through dietary exposure: characterization of Ag nanoparticle formation and dissolution in vivo and toxicokinetic modeling

Abstract: The uptake and depuration of silver nanoparticles (AgNPs) vs. Ag+ by zebrafish (Danio rerio) were investigated using a range of analyses including single-particle ICP-MS (spICP-MS), high resolution-TEM imaging with crystal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 50 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…In our tests, 4.7% of AgNPs was dissolved to Ag + at 50 μg/L and 4.3% for the 500 μg/L AgNP treatment (Figure a), indicating the low solubility of Ag + in AgNPs. Sotiriou et al found that Ag + dissolution occurred rapidly within 5 min, which was far shorter than the exposure time of 24 h. A few earlier studies demonstrated that the rates of uptake of Ag + and AgNPs were comparable in zebrafish. On the basis of the percentage of the Ag dissolution rate and their comparable uptake rates in zebrafish, AgNPs contributed at least 20 times more than the released Ag + . Therefore, we focused primarily on the biological toxicity caused by the AgNP itself and ignored the released trace of Ag + in the medium.…”
Section: Resultsmentioning
confidence: 99%
“…In our tests, 4.7% of AgNPs was dissolved to Ag + at 50 μg/L and 4.3% for the 500 μg/L AgNP treatment (Figure a), indicating the low solubility of Ag + in AgNPs. Sotiriou et al found that Ag + dissolution occurred rapidly within 5 min, which was far shorter than the exposure time of 24 h. A few earlier studies demonstrated that the rates of uptake of Ag + and AgNPs were comparable in zebrafish. On the basis of the percentage of the Ag dissolution rate and their comparable uptake rates in zebrafish, AgNPs contributed at least 20 times more than the released Ag + . Therefore, we focused primarily on the biological toxicity caused by the AgNP itself and ignored the released trace of Ag + in the medium.…”
Section: Resultsmentioning
confidence: 99%